Analysis of Income Tax Accounting Treatment Article 22 for Procurement of Goods at the North Minahasa Education Service - Marvelonita Esther Aras; Inggriani Elim; Syermi S. E. Mintalangi (PT FORMOSA CENDEKIA GLOBAL, 2023)
In Indonesia, tax is an obligation that must be paid by every citizen. One type of income tax collected by the government originating from the APBN/APBD is Income Tax Article 22. This study aims to analyze the accounting treatment of Income Tax Article 22 at the North Minahasa Education Office. The data analysis method used in this research is a qualitative descriptive method. The results of the study show that the calculation of Article 22 Income Tax on the purchase of goods has been carried out properly in accordance with Minister of Finance Regulation Number 34/PMK.010/2017, for the recording of Article 22 Income Tax has been recorded correctly and in accordance with generally accepted principles. The deposit of Article 22 Income Tax has been carried out on time and the Article 22 Income Tax reporting has not been delayed so that it complies with applicable regulations.